Threshold association analysis between residual tumour size and distant metastasis risk after neoadjuvant therapy for rectal cancer: A multicentre retrospective study - Hao Zeng; Xueyi Xue; Dongbo Chen; Xiaojie Wang; Kun Lan; Zhilong Yuan; Wenchang Gan; Baodong Liao; Bozhang Wu; Dongbo Xu; Bing Zeng; Pan Chi; et al. (Colorectal Disease, 2026)
Abstract Purpose This study aimed to perform a threshold analysis of residual tumour size (RTS) to identify the critical threshold influencing distant metastasis (DM), thereby enabling more precise risk stratification. Methods This multicentre retrospective cohort study included patients with locally advanced rectal cancer who underwent radical surgery following neoadjuvant chemoradiotherapy (nCRT). Kaplan–Meier survival curves were plotted and compared using the log‐rank test. Multivariable Cox proportional hazards models were used to identify independent prognostic factors. The threshold‐effect analysis was performed to determine the potential critical point of RTS. Results In this multi‐institutional study, threshold‐effect analysis identified a significant inflection point at 3 cm for the association between RTS and DM risk. Below this threshold, each 1‐cm increase was associated with a markedly higher risk (HR = 1.70, p = 0.015), whereas no significant association was observed above 3 cm ( p = 0.692). Patients with an RTS ≥3 cm exhibited significantly poorer early (≤ 24 months) recurrence‐free survival (RFS) and disease‐free survival (DFS). After 24 months, the pattern was reversed. RTS ≥3 cm was an independent risk factor for both worse RFS (HR = 1.45, p = 0.033) and DM. Subgroup analyses confirmed the consistent negative prognostic impact of RTS ≥3 cm across most strata. Conclusions This study established an objective prognostic threshold for RTS following nCRT. This marks a shift in the understanding of this indicator—from a static association between ‘risk and size’ to a dynamic association between ‘risk and time’.